2020
DOI: 10.1039/d0ra05698g
|View full text |Cite
|
Sign up to set email alerts
|

Storage performance of Mg2+ substituted NaMnPO4 with an olivine structure

Abstract: Magnesium ions have a strong impact on the storage performance of olivine-type NaMnPO4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…[82] The realization of dual Li/ Na intercalation in the full cells operating with Li 4 Ti 5 O 12 anode results in three times higher specific capacities (100 and 60 mAh g À 1 at charge and discharge) in comparison with the full cell working with a single Na intercalation at the cathode and carbon anode (35 and 25 mAh g À 1 ). [82] Another example for higher discharge capacities due to the Li/Na intercalation has been reported in the case of a nanosized NASICON-type Na 3 Fe 2 (PO 4 ) 3 obtained by a mild oxidation of NaFePO 4 maricite (280 °C in the presence of oxygen traces): 150 vs. 90 mAh g À 1 at C/50 rate in Li and Na half-cells, respectively (Figure 4e,f). [81 ] According to ex-situ XRD, HRTEM, and selected area electron diffraction (SAED) studies during the cycling in the Li-electrolytes, the initial NASICON phase Na 3 Fe 2 (PO 4 ) 3 (monoclinic SG C2/ c) undergoes a transformation into lithium NASICON phase having a trigonal structure (R-3) isostructural to Li 3 Fe 2 (PO 4 ) 3 (Figure 4e, f).…”
Section: + /Na + Intercalation Into Polyanion-type Electrodesmentioning
confidence: 98%
See 4 more Smart Citations
“…[82] The realization of dual Li/ Na intercalation in the full cells operating with Li 4 Ti 5 O 12 anode results in three times higher specific capacities (100 and 60 mAh g À 1 at charge and discharge) in comparison with the full cell working with a single Na intercalation at the cathode and carbon anode (35 and 25 mAh g À 1 ). [82] Another example for higher discharge capacities due to the Li/Na intercalation has been reported in the case of a nanosized NASICON-type Na 3 Fe 2 (PO 4 ) 3 obtained by a mild oxidation of NaFePO 4 maricite (280 °C in the presence of oxygen traces): 150 vs. 90 mAh g À 1 at C/50 rate in Li and Na half-cells, respectively (Figure 4e,f). [81 ] According to ex-situ XRD, HRTEM, and selected area electron diffraction (SAED) studies during the cycling in the Li-electrolytes, the initial NASICON phase Na 3 Fe 2 (PO 4 ) 3 (monoclinic SG C2/ c) undergoes a transformation into lithium NASICON phase having a trigonal structure (R-3) isostructural to Li 3 Fe 2 (PO 4 ) 3 (Figure 4e, f).…”
Section: + /Na + Intercalation Into Polyanion-type Electrodesmentioning
confidence: 98%
“…[82] Ex-situ high-resolution transmission electron microscopy (HRTEM) studies reveal that the Li half-cells operate with a dual Li + /Na + intercalation (from the in-situ formed dual electrolyte) into the nano-sized phospho-olivine framework of Mg-NMP as evidenced by the clear differentiation of lithium and sodium phospho-olivine domain structures (LiMnPO 4 and NaMnPO 4 , respectively) in the cycled electrodes. [82] It was also found that the type of the lithium and sodium electrolyte (NaPF 6 , NaTFSI, LiPF 6 , LiBF 4 ) has a significant role on the electrochemical performance, the effect on the specific capacities being more pronounced for the Li-electrolytes of which LiPF 6 (EC/DMC) is the most appropriate (Figure 4c). In Na halfcells a higher discharge capacity and more structured charge/ discharge curves are obtained with NaTFSI in PC (propylene carbonate) containing 5 % NaPF 6 in comparison with pure NaPF 6 electrolyte (Figure 4c).…”
Section: + /Na + Intercalation Into Polyanion-type Electrodesmentioning
confidence: 99%
See 3 more Smart Citations